Platform Power and Regulatory Politics: Polanyi for the 21st Century - Cioffi, John W.; Kenney, Martin; Zysman, John (2021)
The rapid rise, expansion, and growing asymmetric power of online platform firms towards other businesses, labor and even the state itself occurred in a context of minimal regulatory oversight. In many respects, because the existing legal system was handicapped in understanding and regulating the new platform business models. The platform firms undermined traditional industry boundaries and developed surprising synergies by expanding in unexpected ways due to their ability leverage data and computational expertise. The growth of these platforms was accompanied by minimal intervention by state actors until recently, as concerns about the platform firms’ remarkable power has attracted the concern of States globally and the previous regime is giving way to intense debate and increasingly interventionist governmental policies and enforcement actions. We examine several salient aspects of this emerging regulatory and political reaction, and suggest that this represents an attempt to rebalance the positions of social groups in their relationship to the increasingly central platform firms. First, we view the rise of, and recent political responses to, the often-predatory power and manipulative conduct of platform firm in terms of a “Polanyian” double movement in which the destabilizing and destructive effects of unchecked corporate power and market development eventually generates political and regulatory responses to constrain private actions by new economic actors as they threaten the social, political, and economic order. Second, incipient legal changes, most notably the EU’s proposed Digital Markets Act and Digital Services Act, indicate a shift in regulatory emphasis from competition (and antitrust) policy and law, which has proven limited in its capacity to address inherent monopolistic tendencies of platform firms and markets, towards more intensive and encompassing forms of social and economic regulation. Finally, the political dynamics of legal and institutional change open up new possibilities for political economic and societal reordering, but the particular changes will likely vary in character and significance across political jurisdictions, and therefore follow distinctive and possibly divergent developmental trajectories. We hypothesize that the EU may be able to become the first-mover in regulating the powerful multinational platform firms. We recognize that we are at the very beginning of a transformational process that is likely to reorder old and generate new political economic interests, identities, coalitions, and conflicts at the sectoral, national, regional, and international levels.
Keywords: European Union; Platform economy; Polanyi; antitrust; monopoly

Transformation or Structural Change? What Polanyi Can Teach Us about the Platform Economy - Kenney, Martin; Zysman, John; Bearson, Dafna (2020)
The rise of the platform economy marks the latest phase in the ongoing digital revolution. Indeed, the platform is to this digital era what the factory was to the industrial era, both a symbol and an organizing mechanism. Gernot Grabher and Jonas König (2020) used Karl Polanyi’s analysis of what he termed the “great transformation” to frame the rise of platform economy. The platform economy is remarkable as it confirms Polanyi’s (and Marx’s before him) insight that the reach of the market is based upon increased commodification as it has been able to reach into ever more parts of social life. We introduced the term “platform economy” in 2015 because we recognized that the digital platforms were changing the dynamics of capitalist accumulation —- an analysis framed by regulationist school of political economy. The intuition was that the socio-technical innovation of digital online platforms was the critical fulcrum for an economic restructuring that would rewire the flows of data and ultimately money and power. The firms we have termed the “mega-platforms”, Apple, Amazon, Facebook, Google, and Microsoft, have become the most valuable and powerful firms in the world. Importantly, the reach of these platforms is global and yet local and personal. Moreover, this platform power has only been reinforced during the COVID-19 pandemic.
Keywords: COVID-19; Great Transformation; Polanyi; platform economy